2014
DOI: 10.1128/mcb.00980-14
|View full text |Cite
|
Sign up to set email alerts
|

PERK-Dependent Activation of JAK1 and STAT3 Contributes to Endoplasmic Reticulum Stress-Induced Inflammation

Abstract: Neuroinflammation and endoplasmic reticulum (ER) stress are associated with many neurological diseases. Here, we have examined the interaction between ER stress and JAK/STAT-dependent inflammation in glial cells. We show that ER stress is present in the central nervous system (CNS) concomitant with inflammation and astrogliosis in the multiple sclerosis (MS) mouse model of experimental autoimmune encephalomyelitis (EAE). Astrocytes do not easily succumb to ER stress but rather activate an inflammatory program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 195 publications
(188 citation statements)
references
References 70 publications
(83 reference statements)
11
168
0
2
Order By: Relevance
“…Perturbations in the signaling molecules controlling the UPR can lead to functional changes in outcome. For example, we have shown previously (16) and show in Fig. 1 that astrocytes are highly resistant to ER stress.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Perturbations in the signaling molecules controlling the UPR can lead to functional changes in outcome. For example, we have shown previously (16) and show in Fig. 1 that astrocytes are highly resistant to ER stress.…”
Section: Discussionmentioning
confidence: 56%
“…ER Stress Augments Cytokine-induced Gene Expression in a PERK-dependent Fashion-Not only does ER stress stimulate inflammation, it can also alter the response to other inflammatory signals (16,23,24). To test whether PERK inhibition could modulate this effect, astrocytes were treated with the cytokines IL-1␤, OSM, or IFN-␥ individually or in the presence of thapsigargin.…”
Section: Perk Activation Promotes Inflammatory Gene Expression-mentioning
confidence: 99%
See 2 more Smart Citations
“…28) Additionally, protein kinase R-like ER kinase (PERK), an unfolded protein response (UPR) transducer localized to ER membrane, activates STAT3. 29) Moreover, it is reported that calreticulin, a chaperon protein involved in ER stress, promotes invasion and tumorigenesis through the activation of STAT3 signaling. 30) These findings provide evidence that there may be important interaction between ER-ER stress-STAT3 signaling and tumor progression.…”
Section: Discussionmentioning
confidence: 99%